The Effectiveness of the Smart Indonesia Card Program in Reducing the Dropout Rate in Indonesia in 2017–2023: A Literature Study - Rusmiyati, Lena; Ahmad, Masduki; Rochimah, Heni (Journal of English Language and Education, 2025)
This study aims to evaluate the effectiveness of the Indonesia Smart Card (KIP) Program in reducing school dropout rates in Indonesia through a literature review approach. This study was conducted by analyzing various scientific sources such as journal articles, research reports, final projects, and relevant official policy documents, especially those published between 2017 and 2023. The results of the analysis show that the KIP Program contributes significantly to increasing access to and participation in education, especially for students from underprivileged families. The educational financial assistance provided is able to reduce the economic burden on households, thus acting as a preventive instrument against the risk of dropping out of school. However, the effectiveness of this program still faces a number of challenges, including inaccurate targeting of recipients, delays in fund distribution, lack of socialization, and weak monitoring and evaluation systems. In addition, the downward trend in the number of KIP recipients in recent years has been caused by budget rationalization, the impact of the COVID-19 pandemic, and data updates through the Dapodik and DTKS systems. Based on these findings, this study recommends the need to improve distribution policies, increase the accuracy of recipient data, and strengthen coordination between stakeholders in order to optimize the impact of the program on reducing school dropout rates sustainably.